2020
DOI: 10.1177/1558944719900565
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Pattern, and Treatment of Hand Fractures in Children and Adolescents: A 27-Year Review of 4356 Pediatric Hand Fractures

Abstract: Background: The frequency, pattern, and treatment of pediatric hand fractures are rarely reported. We sought to review our institution’s experience in the management of pediatric hand fractures. Methods: A retrospective review of children and adolescents (younger than 18 years) treated for hand fractures between January 1990 and June 2017 was preformed. Fractures were categorized into metacarpal, proximal/middle phalanx, distal phalanx, or intra-articular metacarpophalangeal (MCP)/proximal interphalangeal (PIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…These results correspond well to previously published studies [3,5,6,8]. One of the largest cohorts was reported by Kreutz-Rodrigues and coworkers in 2020 including 4356 pediatric hand fractures; the authors found that almost half of the fractures occurred in the proximal/middle phalanx, but did neither separate these two bones nor report the affected ray in their statistical analysis [5]. Since this study reflects the epidemiological characteristics of the USA, the data is not consistent with the European findings in our investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results correspond well to previously published studies [3,5,6,8]. One of the largest cohorts was reported by Kreutz-Rodrigues and coworkers in 2020 including 4356 pediatric hand fractures; the authors found that almost half of the fractures occurred in the proximal/middle phalanx, but did neither separate these two bones nor report the affected ray in their statistical analysis [5]. Since this study reflects the epidemiological characteristics of the USA, the data is not consistent with the European findings in our investigation.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is an ongoing discussion about the most commonly fractured bone of the child's Communicated by Piet Leroy hand [4]. The proximal phalanx seems to be the most frequently affected [5,6], but in younger children, distal tuft fractures can be even more common [7,8]. Moreover, pediatric hand fractures show a clear male predominance, except in toddlers [8] and are a domain of conservative fracture treatment [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies found that males are more vulnerable than females, older children are more likely to be injured, and the fifth finger and proximal phalanx are more frequently involved, which is similar to our results. In addition, eight out of nine studies reported a higher incidence of sports-related injuries than our series [3–5,7,9,18–20]; and Mirdad [8] reported that crushing is the most common aetiology of PHF. Different fracture characteristics among the studies are likely to be influenced by the different ages and types of activities, including sports, of patients.…”
Section: Discussionmentioning
confidence: 46%
“… 6 7 Many fractures in children will only require a closed manipulation and splint. 8 Nevertheless, as in other locations, there is a limited capacity to remodel angular deformity and no capacity to remodel rotational deformity. 7 Operative fracture fixation, when used, is most commonly achieved through Kirschner (K-wire) insertion, which can be percutaneous or open, or open reduction internal fixation (ORIF) with a plate and screws or lag screws alone.…”
Section: Introductionmentioning
confidence: 99%